Impact of Continuous Positive Airway Pressure Therapy on Body Weight in patients with Obstructive Sleep Apnea - Madiha Moin, Sameera Ali Rizvi, Mirza Saifullah Baig, Faisal Asad, Syeda Hina Rizvi, Ubedullah, (Pakistan Journal of Medical & Health Sciences, 2022)
Aim: To determine the impact of Continuous Positive Airway Pressure therapy on body weight in Obstructive Sleep Apnea patients and assess the relationship between the weight change and other associated symptoms of Obstructive Sleep Apnea. Methods: From a Tertiary care Hospital, Karachi we enrolled 184 Obstructive Sleep Apnea patients of both gender with age more than 18 years of whom 92 patients were exposed to Continuous Positive Airway Pressure while 92 patients were not exposed. In a pre-and post-treatment, information on height, weight, Body mass Index, and neck circumference were recorded. Sleep score was evaluated through Epworth Sleepiness Scale. Results: Results revealed that CPAP effects on weight and BMI. 24% of participants exposed with CPAP gained weight (p=0.03) whereas 72% of participants reduced the weights (p=0.004). The paired t-test showed the mean difference of 3.53±7.5kg (mean±SD, p-value: 0.00). The multivariate analysis showed that CPAP lessens the poor concentration (OR: -4.852; p-value: <0.001), decreases daytime sleepiness (OR: -3.91; p-value: <0.001) and the persons who used dietary plan with CPAP therapy were 6.3 times (p-value: <0.001) more likely to change the weight. Conclusion: The weight of the patient changes with the treatment of OSA after taking a minimum of six months of CPAP therapy. The frequency of weight change in this study population was directed toward weight loss. Elimination of OSA symptoms is directly linked with weight reduction.